2024
DOI: 10.1088/1361-6560/ad222d
|View full text |Cite
|
Sign up to set email alerts
|

How does the electric field induced by tDCS influence motor-related connectivity? Model-guided perspectives

Sofia Rita Fernandes,
M Amparo Callejón-Leblic,
Hugo Alexandre Ferreira

Abstract: Over the last decade, Transcranial Direct Current Stimulation (tDCS) has been applied not only to modulate local cortical activation, but also to address communication between functionally-related brain areas. Stimulation protocols based on simple two-electrode placements are being replaced by multi-electrode montages to target intra- and inter-hemispheric neural networks using multichannel/high definition paradigms. 
Objective: This study aims to investigate the characteristics of electric field (EF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Following the procedure reported in (Fernandes et al 2024), we assumed E-field values larger than 0.15 V m −1 as thresholds values for neuromodulatory effects over the hand knob, based on previous modeling works that reproduced clinical studies where these effects were observed (Yousry et al 1997, Simone et al 2021. As such, we calculated the individual stimulation intensities which led to E-field values larger than 0.15 V m −1 in the hand-knob region for each of the two montages selected.…”
Section: Individual Supra-threshold Stimulation Intensitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the procedure reported in (Fernandes et al 2024), we assumed E-field values larger than 0.15 V m −1 as thresholds values for neuromodulatory effects over the hand knob, based on previous modeling works that reproduced clinical studies where these effects were observed (Yousry et al 1997, Simone et al 2021. As such, we calculated the individual stimulation intensities which led to E-field values larger than 0.15 V m −1 in the hand-knob region for each of the two montages selected.…”
Section: Individual Supra-threshold Stimulation Intensitiesmentioning
confidence: 99%
“…On the other hand, the E-field threshold considered (0.15 V m −1 ) has been selected according to previous experimental Paulus 2000, Lang et al 2004) and modeling studies (Miranda et al 2013, Fernandes et al 2024. However, there is no consensus on a definitive threshold for neuromodulatory effects, which may vary across subjects exhibiting a variety of source dependencies (Ishii et al 2021).…”
Section: Limitations and Future Workmentioning
confidence: 99%